Unsolicited consultation by infectious diseases specialist improves outcomes in patients with bloodstream infection: A prospective cohort study. Issue 6 (December 2018) - Jiménez-Aguilar, Patricia; Romero-Palacios, Alberto; De-la-Calle, Iría-Jesus; Martínez-Rubio, María-Carmen; Girón-González, José-Antonio; Rodríguez-Baño, Jesus
Highlights: Optimal antimicrobial management of patients with bloodstream Infection is complex. Unsolicited consultation by an infectious diseases specialist was related to a higher proportion of days on optimal treatment. . After adjusted analysis, mortality and duration and cost therapy were lower when the recommendations were followed in full. Summary: Introduction: The objective of this study was to evaluate the impact of an intervention based on unsolicited consultations by an infectious diseases specialist (IDS) on the adequacy of antimicrobial treatment and mortality in patients with BSI. Methods: A prospective cohort study was performed in a 410-bed hospital. An intervention based on unsolicited consultation by an IDS for patients with BSI was performed only on days when an IDS was available. Outcomes were the percentage of days on optimal antimicrobial treatment (PDOAT) and mortality. Analyses were performed by linear regression and multivariate logistic regression. Results: Of 400 episodes of BSI included, 292 received the intervention. The median (interquartile range) PDOAT among those with and without the intervention was 93 (6–100) and 0 (0–53), respectively. The intervention was independently associated with a higher PDOAT ( r = 0.5; p < 0.001) but not with mortality. The IDS recommendations were followed in full in 183 episodes, and not in 109. Mortality was 10.4% and 27.6%, respectively. Adherence to recommendations was associated with lower mortality (adjusted OR = 0.3; 95% CI: 0.1–0.5). Conclusions: An intervention based on unsolicited IDS consultation for BSI episodes was associated with improved use of antibiotics and, when the recommendations were fully followed, with lower mortality.